PENERAPAN HYPNOTEACHING DALAM MENGURANGIKESALAHAN SISWA MENYELESAIKAN SOAL PADAPOKOK BAHASAN KUBUS DAN BALOK DI KELASVIII-F SMP NEGERI 7 JEMBER SEMESTER GENAP TAHUN AJARAN 2012/2013 - Ramadhan, Dimas Ardiansyah; Susanto, S; Kristiana, Arika Indah (Kadikma, 2013)
Abstract.The purpose of hypnoteaching method isto make the learning proses more effective and improve the focus of students. This method is also suitable to reduce the student’s mistake in solving problem of cube and cuboid topic. The research subject is VIII-F students of SMP Negeri 7 Jember. The data collection method used in this research isinterview, documentation, observation, and test. The research observed the activity of the teachers and the students. The result shows that the activity of the teachers and the students are significantly increasing. We can conclude that the hypnoteaching method can reduce the students mistake in solving problem of cube and cuboid topic. KeyWords:Hypnoteaching, students mistake, cube and cuboid.